Durable Response and Good Tolerance to the Triple Combination of Toripalimab, Gemcitabine, and Nab-Paclitaxel in a Patient With Metastatic Pancreatic Ductal Adenocarcinoma - Shui, Lin; Cheng, Ke; Li, Xiaofen; Shui, Pixian; Li, Shuangshuang; Peng, Yang; Li, Jian; Guo, Fengzhu; Yi, Cheng; Cao, Dan (Frontiers in Immunology, 2020)
Background: The performance of immune checkpoint inhibitor (ICI) monotherapy was proved to be disappointing in pancreatic ductal adenocarcinoma (PDAC). Increasing evidence has shown the promising efficacy of ICIs combined with systemic therapy in the first-line treatment in solid tumors. Case presentation: We reported a case of a metastatic PDAC patient who had a long-term partial response and good tolerance to the combined approach of toripalimab (a novel PD-1 inhibitor) and gemcitabine plus nab-paclitaxel (GA). PD-L1 positive expression was detected in his liver metastases. Besides, we described a phenomenon of pseudo-progression of this patient during the course of therapy. Conclusion: As the first-line treatment of metastatic PDAC patients, GA plus toripalimab may provide a novel combined approach with favorable response and manageable toxicity. Further clinical trials are needed to confirm the results. Pseudo-progression requires special attention and to be differentiated with true progression in patients undergoing immunotherapy.